KAJIAN STATUS FISIOLOGIS AYAM KAMPUNG DI WILAYAH BANYUMAS DAN KEBUMEN BERDASARKAN PARAMETER LEUKOGRAM TOTAL LEUKOSIT DAN DIFERENSIAL LEUKOSIT - Nur Aini Maulidya; Ismoyowati Ismoyowati; Diana Indrasanti (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The physiological condition of native chickens can be identified by the total leukocyte and leukocyte differential. Leukocytes are part of the body's defense system from infectious diseases. The physiological condition of native chickens can be influenced by several factors, obiter the environment, feed, and maintenance systems. Regional differences between Banyumas and Kebumen regencies as well as extensive and semi-intensive rearing systems are the main factors in this study which aims to examine the physiological status of native chickens based on leukogram parameters, obiter total leukocytes and leukocyte differential. Materials and Methods. The research method used a survey. Determination of the sample was carried out by purposive random sampling, with the criteria of extensive or semi-intensive maintenance, 80 female free-range chickens aged 8-12 months were taken at random. Chicken blood samples were taken from the axillary vein using a 3 cc syringe, then put into a tube containing EDTA. The analytical model used is the General Linear Model (GLM) with the area as a group and the rearing system as a sub group and the number of samples from each farmer as replication. The data obtained will be tabulated, then analyzed using analysis of variance (ANAVA), if the results of the analysis of variance have a significant effect (P <0.05), then proceed with the Honest Significant Difference Test (BNJ). Results. The results of the analysis of variance showed that the area had a significant effect on the total leukocytes of free-range chicken (P<0.05) with the results of the BNJ further test which stated that the Kebumen area had the highest total leukocyte at 10477.5sel/μl, significantly different from the Banyumas area of 9678.7sel/μl. The area that had a significant effect on eosinophils in native chickens (P<0.05) was strengthened by the results of the BNJ further test which stated that the Kebumen area had the highest eosinophils of 5.7%, significantly different from the Banyumas area of 4.9%. Extensive and semi-intensive rearing systems had no significant effect on total leukocytes and leukocyte differential in native chickens (P>0.05). Conclusion. Native chickens reared with extensive and semi-intensive rearing systems in Banyumas and Kebumen Regencies have relatively the same physiological status.